Precise gouging-free tool orientations for 5-axis CNC machining. (January 2015) - Kim, Yong-Joon; Elber, Gershon; Bartoň, Michael; Pottmann, Helmut
Abstract: We present a precise approach to the generation of optimized collision-free and gouging-free tool paths for 5-axis CNC machining of freeform NURBS surfaces using flat-end and rounded-end (bull nose) tools having cylindrical shank. To achieve high approximation quality, we employ analysis of hyper-osculating circles (HOCs) (Wang et al., 1993a, b), that have third order contact with the target surface, and lead to a locally collision-free configuration between the tool and the target surface. At locations where an HOC is not possible, we aim at a double tangential contact among the tool and the target surface, and use it as a bridge between the feasible HOC tool paths. We formulate all such possible two-contact configurations as systems of algebraic constraints and solve them. For all feasible HOCs and two-contact configurations, we perform a global optimization to find the tool path that maximizes the approximation quality of the machining, while being gouge-free and possibly satisfying constraints on the tool tilt and the tool acceleration. We demonstrate the effectiveness of our approach via several experimental results. Highlights: We present an algorithm for generating optimized gouging-free tool path for 5-Axis CNC machining. We employ analysis of hyper-osculating circles that provides third order approximation of the surface. Double tangential contact between the tool and the target surface is employed to connect feasible hyper-osculating tool paths. A robust collision and gouging detection algorithm is provided. We introduce a global optimization algorithm that maximizes the geometric matching between the tool and the target surface.